P196 A rare presentation of subcutaneous Entomophthoramycosis. (20th September 2022) - George, Nimmy Elizabeth; Philip, Achu Jacob; E., Arthi; Asir, Johny; Kindo, Anupama Jyoti; Nair, Shashikala
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Entomophthoramycosis is a chronic granulomatous type of subcutaneous infection seen mainly in immunocompetent individuals. The usual focus of Conidiobolomycosis infection is as rhinoentomophthoramycosis, characterized by chronic, indolent, and localized swelling of the nose, paranasal tissues, sinuses, cheeks, and upper lips and it infrequently affects the lower extremities.  : We report a case of subcutaneous Conidiobolomycosis in a 21-year-old male with an alleged history of trauma to left foot by a wooden stake 6 months back. Primary treatment of the wound was done at a local hospital. A total of 4 months post-trauma he developed multiple pus discharging sinuses on the dorsal and plantar aspects of the left foot, for which local dressing was done in a nearby hospital. He presented to our hospital with non-healing multiple sinuses, with active serosanguinous discharge. He underwent wound debridement under spinal anesthesia and tissue was sent for fungal culture, histopathological examination.  : Aerobic culture of the wound swab revealed moderate growth of Methicillin-resistant Staphylococcus aureus sensitive to clindamycin, gentamicin, and linezolid. Histopathological examination of the tissue showed a resolving abscess with granulation tissue. Direct microscopic examination of the tissue by KOH mount showed no fungal elements. It was inoculated into Sabouraud's dextrose agar with and without cycloheximide and incubated at both 25°C and 37° C. Sabouraud's dextrose agar without cycloheximide incubated at 37°C after 48 h of incubation grew cream-colored glabrous colonies adherent to surface with pale reverse. Lactophenol cotton blue preparation revealed broad, sparsely septate hyphae with primary conidia which are globose approx. 40  μ m is diameter, produced singly. They have a characteristic protruding papilla on one side. The fungal isolate was identified as Conidiobolus species. Sequencing results are awaited for species identification and confirmation.  : Serial wound dressings were done following strict infection control policies and he was started on tablet linezolid 600 mg twice daily, tablet itraconazole 400 mg twice daily for 1 week, followed by 400 mg once daily for 6 months.  : Conidiobolus is a soil saprophyte, found in decaying vegetation in most warm climates in tropical countries. There has been only one published case report of subcutaneous entamophthoramycosis of the foot, in a 49-year-old female from Venezuela. To the best of our knowledge, we report the first case of subcutaneous entamopthoramycosis of the lower extremity in India and the second case in the world.